Вещий князь: роман : в 4-х кн. (Андрей Посняков) - Посняков Андрей (Новые Супергерои)
Экземпляры: (20130212) / Инвентарный номер: 48313 / Цена: 161.70 / Сис.шифр: Р2 / Авт.знак: П 62 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6